Tritium accumulation and preservation into clay minerals for environmental protection - Kartashov, V.V.; Kovalenko, G.D.; Letuchi, A.N.; Samodurov, V.P.; Vitko, V.I. (Вопросы атомной науки и техники, 2004)
The comparative analysis of new and previously received data is represented, which allows us to estimate the influence of hydrodynamic conditions on tritium accumulation and retention in clay minerals. We have received time dependence of the tritium exchange process with the hydrogen of natural clay mineral matrix, long time halfcycle tritium capture by clay, the part of total tritium activity captured by clay for long time (more then 1 year). The received data and mathematical modeling let us determine the mineral component of natural clay, which more efficiently captures and retains tritium and is the best component for making barrier near radioactive tritium waste repository.